Impact of ironing on indoor particle levels and composition. (April 2021) - Vicente, Estela D.; Evtyugina, Margarita; Vicente, Ana M.; Calvo, Ana I.; Oduber, Fernanda; Blanco-Alegre, Carlos; Castro, Amaya; Fraile, Roberto; Nunes, Teresa; Lucarelli, Franco; Calzolai, Giulia; Alves, Célia A.
Abstract: Domestic chores are an important part of the household's daily routine and can contribute significantly to personal exposure. In this study, the particulate mass and number concentrations were assessed when using two irons (steam iron and steam iron with boiler) under distinct conditions (minimum ventilation and indoor doors open) and in the background air. The detailed PM10 chemical characterisation included organic and elemental carbon, elements and organic speciation. Particle number emission rates ranged from 8.1 ± 0.09 × 10 11 to 15 ± 3.5 × 10 11 particles min −1 . Ratios of peak to background levels indicate that ironing can elevate the ultrafine particle number concentrations by a factor ranging from 35 to 194. PM10 emission rates from steam iron, under minimum ventilation conditions (6.6 ± 1.4 μg s −1 ), were higher than those from steam iron with the doors open (1.9 ± 1.6 μg s −1 ). The highest particle number and mass emission rates were recorded when the steam iron with boiler was used. Regarding the chemical composition of particles, elemental carbon and strontium were only detected during ironing. Bromide concentrations increased noticeably over background levels (9–51 times) during ironing. PM10 samples encompassed a wide range of organic compounds, part of which can be attributed to the handling of textiles and the use of detergents, fabric softeners, cosmetics and personal care products. Substances emitted by volatilisation or shedding of textile fibres, or due to handling, can contribute to human exposure through inhalation. The cancer risks associated with inhalation of metals and PAH were found to be negligible. Highlights: Iron type and ventilation condition had a great effect on PM mass and number emissions. Household exposure to PM can be reduced by proper space ventilation. Elemental carbon and strontium were only detected during ironing. Clothes handling and heating can release a large number of organic compounds. The inhalation cancer risk for metals and PAHs was negligible.